2011
DOI: 10.1007/s00284-011-0068-1
|View full text |Cite
|
Sign up to set email alerts
|

Class 2 Integrons Dissemination Among Multidrug Resistance (MDR) Clones of Acinetobacter baumannii

Abstract: Acinetobacter baumannii has emerged as a serious problem in the hospital environment at a global scale. Previous results from our laboratory showed a high frequency of class 2 integrons in A. baumannii strains from Argentina regarding the low rate of this element in A. baumannii isolates from the rest of the world. To reveal the current epidemiology of class 2 integrons, a molecular surveillance analyzing 78 multidrug resistant (MDR) A. baumannii isolates from Argentina and Uruguay was performed, exposing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…In Argentina, this array was also frequently observed (5), and this finding is in line with the report of the CC113/79 spread in this country (14). Similarly, the description of dfrA1, sat2, and aadA1 cassettes in Argentina, Chile, and Uruguay may also be explained by the CC113/79 spread in Latin America (5, 7).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…In Argentina, this array was also frequently observed (5), and this finding is in line with the report of the CC113/79 spread in this country (14). Similarly, the description of dfrA1, sat2, and aadA1 cassettes in Argentina, Chile, and Uruguay may also be explained by the CC113/79 spread in Latin America (5, 7).…”
supporting
confidence: 76%
“…This finding is possibly related to local clonal groups (6), but a hypothesis has not yet been addressed. The class 2 integron structure seems less diverse than that of class 1 (7) and is usually embedded within transposon Tn7 (5,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Class 2 integrons were also found in all the indigo-pigmented A. baumannii strains, whereas no class 1 integrons were found. These results are in accordance with our previous studies, which showed that class 2 integrons are more abundant than class 1 integrons in A. baumannii strains from Argentina (20,29,30). PCR cartography and sequence analyses revealed that In2-7, which is the common class 2 integron array, was present in the 13 strains studied (20,29).…”
Section: Resultssupporting
confidence: 82%
“…Also, Kamalbeik et al showed that 7.5% and 67.5% of the strains contained class I and II integrons, respectively [23]. In the studies carried out by Ramírez et al [24] and Martins et al [25], the prevalence of class II Integron was 23% and 41.7%, respectively. In the research conducted by Taherikalani et al (Tehran at 2012) [26] and Moammadi et al (west of Iran at 2012) [27] the frequency of class I, II, and III integrons was 85%, 14%, and 0%, and 97%, 31%, and 0%, respectively.…”
Section: Discussionmentioning
confidence: 99%